New Internet communication technologies in Polish sports organizations - Gajek, Katarzyna (Business Informatics, 2014)
There are three goals of this article. First is to identify the most popular forms of internal and external communication based on computer technologies in an organization. The second goal is to underline the need of improvement in the field of competence in the use of NICT through understanding the purpose and scope of each medium. The third aim is to reveal how sport organizations and Polish sport organizations deal with NICT in their communication practice. Literature review is the main method of collecting data concerning the most often used NICT solutions by the organizations. The last part, focused on the NICT used in Polish sport organizations, is based on the available international literature and introductory results of the analysis of media used by Polish sport organizations in the processes of internal and external communication
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 4 (34), s. 37-46
Keywords: New Internet communication technologies; sport organization; organizational communication; nowe internetowe technologie komunikacyjne; organizacja sportowa; komunikacja w organizacji